Migraine and endovascular closure of patent foramen ovale as a method of its treatment: a literature review - A. S. Tereshchenko; E. V. Merkulov (Кардиоваскулярная терапия и профилактика)
The literature review is devoted to the pathophysiology and clinical picture of migraine, targets of therapy and drugs used, and the connection between the pathogenesis of migraine with aura and patent foramen ovale is discussed. The results of clinical studies show a positive effect of endovascular patent foramen ovale closure on the course of migraine in the form of a decrease in the intensity, frequency of attacks and the number of headache-free days, as well as in some cases complete relief of the disease. Further study of the topic is promising, but requires careful study design and long-term follow-up of patients.